The Probe Team [episode no. 308] (Probe Productions, 1994)
The first part is about the issue on formalin present in vegetables we buy in the market. General Agreement on Tariff and Trade is discussed on the part. The third part is about the TALA, a jazz group who represent the Philippines in the North Sea Jazz Festival.